(untitled) (REMUNOM, 2026)
This scientific article analyzes freedom of expression within the context of Brazilian Electoral Law. Starting from its recognition as a fundamental right and a pillar of the Democratic Rule of Law in the 1988 Constitution, the study examines the tension between the free exercise of political expression and the limits required to protect the fairness, legitimacy, and balance of the electoral process. Through qualitative research, including bibliographic review and analysis of judicial decisions, the study investigates the boundaries between legitimate political criticism and unlawful practices such as negative electoral propaganda, hate speech, and disinformation (fake news) in the digital environment. The analysis shows that the jurisprudence of the Supremo Tribunal Federal and the Tribunal Superior Eleitoral has increasingly recognized freedom of expression as a preferred constitutional position, adopting a standard of minimal intervention while acting firmly against abuses that may threaten the integrity of elections and democratic institutions. The study concludes that the contemporary challenge lies in regulating new communication technologies in a way that preserves a free and plural public debate, without allowing freedom of expression to become an instrument for undermining democracy itself.